Socialization of Independent Learning in Science Learning - Srinatalia Silaen (MOVE: Journal of Community Service and Engagement, 2023)
IPA Learning Objectives Independent Curriculum, namely teaching according to ability level is a learning approach that is centered on students based on their level of ability, not on class level. One of the trainings is training on the socialization of science learning with the concept of independent learning as well as improving the soft skills of HKBP TOMUAN PRIVATE ELEMENTARY SCHOOL teachers. The purpose of this service is to develop the concept of independent learning at HKBP TOMUAN PRIVATE ELEMENTARY SCHOOL through training workshops and socialization of independent learning so that this learning can run better. Theoretical benefits add knowledge and insight into science learning, add experience to the concept of learning science. The results of this service are expected to assist teachers in utilizing science teaching media technology at this time, schools: The results of this study are expected to be a reference for applied to every science laboratory learning process in schools.